2021
DOI: 10.1073/pnas.2115089118
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging of intraflagellar-transport turnarounds reveals that motors detach, diffuse, and reattach to opposite-direction trains

Abstract: Intraflagellar transport (IFT), a bidirectional intracellular transport mechanism in cilia, relies on the cooperation of kinesin-2 and IFT-dynein motors. In Caenorhabditis elegans chemosensory cilia, motors undergo rapid turnarounds to effectively work together in driving IFT. Here, we push the envelope of fluorescence imaging to obtain insight into the underlying mechanism of motor turnarounds. We developed an alternating dual-color imaging system that allows simultaneous single-molecule imaging of kinesin-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 66 publications
1
33
1
Order By: Relevance
“…To date, the major reported target of ICK and CDPK1 is kinesin-2 (Chaya et al, 2014; Liang et al, 2014), which is proposed to dissociate from the IFT train upon phosphorylation (Liang et al, 2014). Kinesin-2 dissociation may initiate the major conformational change that IFT trains undergo as they convert to retrograde trains (Chien et al, 2017; Jordan et al, 2018; Stepanek and Pigino, 2016; Wingfield et al, 2021; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the major reported target of ICK and CDPK1 is kinesin-2 (Chaya et al, 2014; Liang et al, 2014), which is proposed to dissociate from the IFT train upon phosphorylation (Liang et al, 2014). Kinesin-2 dissociation may initiate the major conformational change that IFT trains undergo as they convert to retrograde trains (Chien et al, 2017; Jordan et al, 2018; Stepanek and Pigino, 2016; Wingfield et al, 2021; Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that requires a closer inspection are the binding and unbinding kinetics of IFT motors to and from IFT trains ( Figure 5 ). A recent single-molecule study in C. elegans has revealed that the interaction of IFT motors with IFT trains is highly dynamic [ 142 ]. Heterotrimeric kinesin-II motors were shown to stochastically detach from anterograde trains, switching from a directed to a diffusive state (likely autoinhibited).…”
Section: Ift Regulation From the Perspective Of The Motorsmentioning
confidence: 99%
“…s %" ), diffusion coefficients (𝐷: 0.01 -1.8 µm $ . s %" ), integration times (∆𝑡: 30, 60, 100 ms) and localization precision (𝑃𝐿: 0, 30, 60, 90 nm), reflecting typical values we have obtained in single-molecule trajectories of ciliary components in the chemosensory cilia of C. elegans (20)(21)(22). For each data set, we simulated 20 XY-trajectories of 200 steps (see parameters in Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, the location of the turnaround, whether the turnaround contains a pause or not, what the duration of this pause is, and whether the motor is diffusing during the pause can be extracted. We have applied this wMSDc analysis approach to a complete data set as mentioned above (20).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation